The Diffuse Autonomy. The Rosario Highschool in the projects of the public university in the XIXth Colombian century - Bohórquez, Julio Gaitán Bohórquez Gaitán (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
The article explores in normative primary sources the institutionally and the autonomy of Rosario High school in Bogotá during the 19th century, to show their relationship with the Republican State as well as the different moments that the process of the establishment of the new education system had to struggle with and which through various projects and models was attempted in the midst of a great economic and social contingencies.